Burnout and Job Satisfaction Among Islamic Religious Knowledge Teachers in Brunei Darussalam - Gamal Abdul Nasir Zakaria; Salwa Mahalle; Nor Zaiham Midawati Abdullah; Muhamad Afifuddin Ghozali; Maryam Nuramalia (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
This study aimed to identify the level of burnout (emotional desolation, depersonalization, and personal accomplishment) and job satisfaction (job type, salary, promotion opportunities, supervisory, and collea-gues) among teachers of religious education in Brunei Darussalam (referred to as IRK teachers in this study). This study involved 238 teachers who are teaching the Islamic Revealed Knowledge (IRK) subject in all the government secondary schools in Brunei Darussalam. Instruments used for data collection, namely the Mas-lach Burnout Inventory and the Job Descriptive Index (JDI). In this study, results showed that the level of burnout of the IRK teachers is at a moderate level which gives an indication that most of them were able to control their emotions although their career as teachers is very challenging and tiring. Another factor that could contribute to this phenomenon is that the level of job satisfaction among the teachers is high, especi-ally in the aspect of promotion and colleagues. Hence, colleagues at the workplace could affect the teachers’ burnout level because they see their colleagues as supportive and continuously give them strong moral sup-port. Not only is human-to-human support needed to positively handle the burnout level, but it also needs institunionalized programs to improve the general climate and relatiop with the colleagues.